Altruistic leadership and trust in leaders at the public housing and residential areas service of Madiun City - Srimulyani, Veronika Agustini; Nathalie, Malfilia (Priviet Social Sciences Journal, 2025)
Trust is essential to improve leadership and organizational effectiveness. Since successful leadership is essential to an organization’s success, the most crucial element influencing subordinates’ trust in a leader is the leader’s personal qualities. A connection between a leader and their subordinate that is founded on equality, dedication, collaboration, mutual respect, and dependability is known as trust in leaders. This study aims to experimentally explore the connection between altruistic leadership and trust in leaders. The respondents of the study were 34 State Civil Apparatus assigned to the Public Housing and Residential Areas Service of Madiun City. Data collection used a questionnaire that was administered directly to the respondents. Data analysis used the help of Smart PLS software version 3. The findings of the analysis indicate a strong positive impact of altruistic leadership on trust in leaders. Based on the study’s findings, leaders and followers can establish a mutually advantageous relationship in which leaders’ selfless actions foster trust in followers.